Kontaminasi Koliform pada Daging Ayam Broiler di Pasar Tradisional Sentani Kabupaten Jayapura - Sadi, Ristasari (BPFP Universitas Bengkulu, 2023)
The purpose of this study was to evaluate the level of bacterial contamination in broiler meat at the Sentani Jayapura traditional market by testing the total number of coliform bacteria. Sampling was carried out thoroughly among broiler chicken sellers at the Sentani Traditional market in Jayapura. Seven samples were from the Pharra market and three samples from the Lama market, so the total of broiler meat samples was 10 samples. Test result data is presented in the form of an average of contaminated samples, with descriptive analysis of the number of coliforms. The research results showed that the average amount of coliform in the Pharra market was 1.5 x 106 CFU/gram and the Lama market was 2.7 x 102 CFU/gram. It was concluded that traders in the Sentani traditional market, Jayapura Regency, did not apply hygiene measures during the selling process, resulting in chicken meat being contaminated with coliform bacteria. Keywords: Coliform, Broiler Chicken Meat, Traditional Markets ABSTRAK Tujuan dalam penelitian ini adalah untuk mengevaluasi tingkat kontaminasi bakteri pada daging broiler di pasar tradisional Sentani Jayapura dengan menguji jumlah total bakteri koliform. Pengambilan sampel dilakukan secara menyeluruh terhadap penjual ayam broiler di pasar Tradisioanal Sentani Jayapura. Tujuh sampel dari pasar Pharra dan tiga sampel dari pasar Lama, sehingga total sampel daging broiler sebanyak 10 sampel. Data hasil pengujian disajikan dalam bentuk rataan sampel yang terkontaminasi, dengan analisis deskriptif jumlah coliform. Hasil penelitian menunjukkan bahwa rataan jumlah koliform di pasar Pharra sebesar 1,5 x 106 CFU/gram dan pasar Lama sebesar 2,7 x 102 CFU/ gram. Disimpulkan bahwa pedagang di pasar tradisional Sentani Kabupaten Jayapura tidak menerapkan tindakan kebersihan pada saat proses penjualan sehingga mengakibatkan daging ayam terkontaminasi bakteri koliform. Kata kunci: Koliform, Daging Broiler, Pasar Tradisional